Accelerating gifted Filipino children: Considerations and challenges - Tyrone O. Gil Jr. (Universitas Pendidikan Indonesia, 2025)
This study underscores the importance of nurturing intellectually advanced Filipino youth as a catalyst for national development and innovation. It addresses the underutilization of gifted education in the Philippines, shaped by cultural, socio-economic, and systemic challenges. The objective is to evaluate the effectiveness of academic acceleration strategies and examine how gifted students and their families perceive them. Using a systematic literature review, policy analysis, and theoretical frameworks, the study investigates methods such as subject-based acceleration, grade skipping, early entrance, curriculum compacting, telescoping, and radical acceleration. Findings indicate that these approaches foster not only academic achievement but also socio-emotional benefits, including greater satisfaction, stronger self-concept, and reduced disengagement. The research challenges misconceptions that acceleration harms students, showing instead that obstacles stem from weak policies, insufficient teacher training, and inconsistent practices. The paper concludes that a paradigm shift is necessary through culturally sensitive identification, stronger policies, and sustained support to maximize the potential of gifted learners. Abstrak Penelitian ini menekankan pentingnya pengembangan anak-anak berbakat intelektual di Filipina sebagai penggerak pembangunan nasional dan inovasi. Isu utama yang diangkat adalah masih kurangnya pemanfaatan pendidikan bagi anak berbakat akibat kendala budaya, sosial-ekonomi, dan sistemik. Tujuan penelitian ini adalah mengevaluasi efektivitas strategi percepatan akademik serta memahami persepsi murid berbakat dan keluarganya terhadap pendekatan tersebut. Melalui tinjauan pustaka sistematis, analisis kebijakan, dan penerapan kerangka teoretis, penelitian ini mengkaji berbagai metode, seperti percepatan berbasis mata pelajaran, loncat kelas, masuk sekolah lebih awal, pemadatan kurikulum, telescoping, dan percepatan radikal. Hasil penelitian menunjukkan bahwa strategi ini tidak hanya meningkatkan capaian akademik, tetapi juga memberikan manfaat sosial-emosional, seperti kepuasan belajar, penguatan konsep diri, dan berkurangnya kejenuhan. Penelitian ini menantang anggapan bahwa percepatan merugikan murid, dengan menegaskan bahwa hambatan justru muncul dari lemahnya kebijakan, kurangnya pelatihan guru, dan praktik yang tidak konsisten. Kesimpulannya, diperlukan perubahan paradigma melalui identifikasi yang peka budaya, kebijakan yang lebih kuat, serta dukungan berkelanjutan untuk mengoptimalkan potensi murid berbakat. Kata Kunci: akselerasi; anak berbakat Filipina; pendidikan anak berbakat; strategi akselerasi